HUBUNGAN CARA PERSALINAN TERHADAP PREVALENSI KOLONISASI STAPHYLOCOCCUS AUREUS PADA NEONATUS DI RUANG PERINATOLOGI RSIA PURI BETIK HATI - Nadira Rahil Rachmawani; Tri Umiana Soleha (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2019)
ABSTRACT Background. Neonates with normal parturitition have a tendency to colonized by Staphylococcus aureus higher than neonates with perabdominal parturitition, this case may occur due to the bacteria present in the mother's birth canal. Staphylococcus aureus colonization can lead to serious infections. The purpose of this study was to examine the relationship of types of parturitition to the prevalence of colonization of Staphylococcus aureus in neonates. Methods. This is an analytical research with cross sectional approach using primary data with laboratory examination. Sampling was conducted in the perinatology room of RSIA Puri Betik Hati in 2017 and was taken using consecutive sampling with total sample is 62 samples that fulfill the inclusion criteria and exclusion criteria. Results. The result of this research is, there is relation between types of parturitition and the prevalence of colonization of Staphylococcus aureus in neonates in Perinatology Room of RSIA Puri Betik Hati with p value = 0,001 where bacterial colonization is more common in neonates who are born with normal parturitition. Conclusion. The types of parturitition affects the prevalence of colonization of Staphylococcus aureus in neonates.